Umbrella use as a public health adaptation strategy to reduce urban heat stress exposure - Reischl, Uwe; Goonetilleke, Ravindra S. (International Journal of Scientific Reports, 2025)
Background: Urban heat stress is a growing public health concern due to global warming. Tree planting is being promoted in urban areas as a public health heat-stress mitigation strategy. Use of personal umbrellas is considered as a low-cost, and highly adaptable alternative to trees. Several cities around the world have established programs providing umbrellas to residents. The goal of this study was to assess how the use of umbrellas compares to the effectiveness of tree shade and how such an approach can serve as a public health adaptation strategy. Methods: The effectiveness offered by tree shade and personal umbrella shade was investigated. A field study was conducted employing wet bulb globe temperatures (WBGT) monitors, a ultraviolet (UV) radiation sensor, and a light intensity meter. Heat stress, UV radiation and visible light attenuation were measured for ten tree shades and six umbrella shades. Simultaneous measurements of both shade and direct sunlight exposure were performed to achieve controlled measurement conditions. Results: The study showed that umbrella shade provided a reduction of visible light similar to tree shade (91% vs. 93%)/, a reduction in UV radiation (94% vs. 90%), and a reduction in WBGT heat stress (24% vs. 18%). Conclusions: The study showed that personal umbrellas can provide protection against solar radiation in urban settings equivalent to trees and, therefore, can be used as a viable public health adaptation strategy to reduce excessive heat stress exposure in urban environments.